Strategic interactions, affective reactions, and fast adaptations - Kareev, Yaakov; Avrahami, Judith; Fiedler, Klaus (Journal of experimental psychology, 2014)
We studied repeated choices under uncertainty in situations in which the source of uncertainty is the choice of an interaction partner. In 1 experiment the participants engaged in repeated decisions in a mixed motive game; in another experiment the options and outcomes were identical to those in the 1st, but periods of the mixed-motive game alternated with periods of a coordination game, with the change in period not announced. We analyzed choice dynamics-the relationship between an outcome and the choice that followed-and aggregate choice probabilities to gauge the relative merit of reward-based or affect-based accounts (the affects considered being disappointment and regret). In both experiments choice dynamics were essentially identical and were compatible with only the regret-based account. This was true irrespective of the game played or the stage (early or late) of the game. Moreover, the same dynamics explained the very different aggregate probabilities with which the 2 options were chosen in the 2 games and the remarkably fast adaptations to unannounced changes in the game played. (PsycINFO Database Record (c) 2013 APA, all rights reserved).